Mortality pattern of silicotic subjects in the Latium region, Italy. Issue 12 (December 1989) - Forastiere, F; Lagorio, S; Michelozzi, P; Perucci, C A; Axelson, O
Abstract : A mortality study was carried out on 595 workers who were compensated for silicosis in the Latium region, Italy, during the period 1946-84 who died between 1 January 1969 and 31 December 1984. Respiratory disorders, tuberculosis, lung cancer, bone cancer, and cirrhosis of the liver showed significantly increased risk ratios (4.1, 3.7, 1.5, 4.1, and 1.9 respectively); excesses of brain cancer and leukaemia did not reach statistical significance. Lung cancer mortality was further analysed by age, period of compensation, final degree of disability, and occupational activity. The possible confounding role of smoking was assessed by comparing the lifetime smoking habits of a sample of silicotic subjects with those of the general male population as estimated by a national health survey; the prevalence of ever smokers among silicotic subjects (70.7%) was similar to that estimated for the general population (68.5%). The present study indicates that silicosis is associated with lung cancer even though it does not clarify the respective roles of exposure to silica and silicosis.